2014
DOI: 10.1007/s11523-014-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

The HSP90 inhibitor ganetespib potentiates the antitumor activity of EGFR tyrosine kinase inhibition in mutant and wild-type non-small cell lung cancer

Abstract: Small molecule inhibitors of epidermal growth factor receptor (EGFR) tyrosine kinase activity, such as erlotinib and gefitinib, revolutionized therapy for non-small cell lung cancer (NSCLC) patients whose tumors harbor activating EGFR mutations. However, mechanisms to overcome the invariable development of acquired resistance to such agents, as well as realizing their full clinical potential within the context of wild-type EGFR (WT-EGFR) disease, remain to be established. Here, the antitumor efficacy of target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 48 publications
(61 reference statements)
0
28
0
Order By: Relevance
“…However, these kinases are clients of, and binding strongly to HSP90 [173]. It is therefore not surprising that HSP90 inhibitor Ganetespib, combined with inhibitor Gilotrif of such kinases would reduce the synthesis of other HSPs other than HSP90 (because HSP90 is bound to heat shock factor 1; see Figure 2), and would enhance the inhibition of the mTORC1 pathway, causing stronger anti-cancer effects (as compared to the situation using Gilotrif alone) in in vivo mice model study reported [174], in our opinion.…”
Section: Targeting Hsp90 Alonementioning
confidence: 99%
“…However, these kinases are clients of, and binding strongly to HSP90 [173]. It is therefore not surprising that HSP90 inhibitor Ganetespib, combined with inhibitor Gilotrif of such kinases would reduce the synthesis of other HSPs other than HSP90 (because HSP90 is bound to heat shock factor 1; see Figure 2), and would enhance the inhibition of the mTORC1 pathway, causing stronger anti-cancer effects (as compared to the situation using Gilotrif alone) in in vivo mice model study reported [174], in our opinion.…”
Section: Targeting Hsp90 Alonementioning
confidence: 99%
“…Compared to the routine combination therapy that blocks the bypassed signals concomitantly, inhibition of Hsp90 offers a more feasible and effective way to overcome resistance because the kinases accounting for gefitinib resistance retain a high affinity for Hsp90 binding [31] . Notably, multiple recent preclinical and clinical investigations have highlighted the potential of the application of Hsp90 inhibitors such as NVP-AUY922 and ganetaspib to suppress the proliferation of gefitinib-resistant cells [32][33][34][35][36] .…”
Section: Original Articlementioning
confidence: 99%
“…The strong HSP90/EGFR interaction has then been used to propose an alternative therapeutic strategy combining an HSP90 inhibitor with an EGFR inhibitor. Interestingly, this combination (with the EGFR inhibitor erlotinib) resulted in prolonged animal survival in nonmutated and erlotinib-resistant models [67,68,70,71,114,115].…”
Section: Hsp90 and Erbb Family Of Receptor Tyrosine Kinase (Rtk)mentioning
confidence: 99%